Cake pop crush eaudiobook A wish novel. - Nelson, Suzanne (Wish, 2019)
Sometimes friends, school, and boys can be a recipe for disaster! Alicia Ramirez has always loved baking. Her family owns Say It With Flour, the small bakery in town. And Ali's specialties are cake pops: delicious confections on a stick. But Ali's sweet life turns sour when a sleek coffee shop opens across the street, giving her bakery a run for its money. Worst of all, the owner's son, Dane McGuire, likes to bake, too. He's the new kid in Ali's school . . . and happens to be annoyingly cute. When Dane and Ali engage in a bake-off to prove who is the cake-pop master, it's Ali's chance to save Say It With Flour. But will she be able to rise to occasion . . . and ignore what her heart might be telling her?